PENGARUH DEBT TO EQUITY RATIO DAN GROSS PROFIT MARGIN TERHADAP HARGA SAHAM PADA PT VALE INDONESIA TBK PERIODE 2013-2023 - Paulina, Vanka; Lisdawati, Lisdawati (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The objectives of this study are: (1) to determine whether the Debt to Equity Ratio (DER) has an effect on stock prices at PT Vale Indonesia, Tbk.; (2) to determine whether the Gross Profit Margin (GPM) has an effect on stock prices at PT Vale Indonesia, Tbk.; and (3) to determine whether the Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) together have an effect on stock prices at PT Vale Indonesia, Tbk. The research method used in this study is a quantitative method. The data sample consists of secondary data in the form of annual financial statements of PT Vale Indonesia Tbk for the period 2013–2023, obtained through literature-based observation. The data analysis techniques used include descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study show that: (1) partially, GPM has a significant negative effect on stock prices at PT Vale Indonesia, Tbk, with a significance value of 0.021 < 0.05 and a t-value greater than the t-table -2.875 > 2.306; (2) partially, DER has a significant positive effect on stock prices at PT Vale Indonesia, Tbk, with a significance value of 0.040 < 0.05 and a t-value greater than the t-table 2.455 > 2.306; and (3) simultaneously, DER and GPM have a significant positive effect on stock prices at PT Vale Indonesia, Tbk, with an F-test value of 0.015 < 0.05 and an F-value greater than the F-table 7.418 > 4.46.